The Interesting Side of the Birth of a Demonstrator Mansur Samin in Ian Watt's Social Perspective - Moch. Fachrul Mustika; Jumiati Lanta; M. Nurzin R. Kasau (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2024)
The material object of this research is Mansur Samin's social criticism in his poem entitled